(untitled) (Revista Latino-Americana de Enfermagem, 2003)
Based on some articles in the journal Nursing Ethics, the author outlines some of the areas of major importance for nursing in the future. These areas - the care of elderly people, long-term home-based care, genetics, international research and conflict and war - demand a new voice of nursing, which is a political voice. The rationale for a political voice is the ICN Code of ethics for nurses and the fourfold responsibilities laid on nurses: to promote health, to prevent illness, to restore health, and to alleviate suffering. Some indications are given on how nurses can engage in political work.